The Effect of Assistive Training Devices on the Development of Physical Abilities and Their Relationship to Technical Skills in Futsal Players with Mild Intellectual Disabilities - Shneair, Thaer Saleh (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This study investigates the role of assistive training devices and exercises in improving selected physical abilities—namely speed, strength, flexibility, and coordination—among futsal players with mild intellectual disabilities. It further examines how these physical enhancements contribute to the development of core futsal skills, including passing, receiving, dribbling, and shooting. The research establishes the relationship between physical development and technical performance, providing a structured training framework that incorporates assistive tools as effective means of enhancing both athletic and functional outcomes. The findings highlight the importance of adaptive training interventions in promoting physical and skill-based progress, ultimately improving daily functional performance and fostering greater inclusion of individuals with mild intellectual disabilities in sports.